Pelaksanaan Otonomi Daerah dan Desentralisasi Fiskal di Indonesia (Studi Kasus: Kabupaten/Kota di Provinsi Jawa Tengah) - Vebrina Hania Cholily (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Granting regional autonomy is an effort to empower the region in order to manage development in the region. Regional Autonomy in Indonesia still has obstacles that make the Implementation of Regional Autonomy in Indonesia not 100% evenly distributed. This is due to several factors, namely the differences in the regional autonomy paradigm, the strong bureaucratic paradigm, the weak control of representatives of the people and the community and strategic errors. Likewise in Central Java. This research is a case study with a documentation method and a descriptive qualitative analysis. The results of this study are that the obstacles that often occur in the implementation of regional autonomy in districts/cities in Central Java are due to the fact that PAD has not been maximized and there has been a decrease in PAD in 2020. There are even those who are experiencing a budget vacuum in the APBD. This certainly can be an evaluation for the government in determining policy.